2012
DOI: 10.1016/j.cviu.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Composed complex-cue histograms: An investigation of the information content in receptive field based image descriptors for object recognition

Abstract: Recent work has shown that effective methods for recognizing objects and spatio-temporal events can be constructed based on histograms of receptive field like image operations.This paper presents the results of an extensive study of the performance of different types of receptive field like image descriptors for histogram-based object recognition, based on different combinations of image cues in terms of Gaussian derivatives or differential invariants applied to either intensity information, colour-opponent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 47 publications
1
37
0
1
Order By: Relevance
“…More recently, Larsen et al [81] made use of multi-local N-jet descriptors that do not rely on a spatial statistics of receptive field responses as used in the SIFT and SURF descriptors or their analogues. A notable observation from experimental results is that very good performance can be obtained with coarsely quantized even binary image descriptors (Pietikäinen et al [131], Linde and Lindeberg [88], Calonder et al [26]). Moreover, Zhang et al [158] have demonstrated what can be gained in computer vision by considering biologically inspired image descriptors.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Larsen et al [81] made use of multi-local N-jet descriptors that do not rely on a spatial statistics of receptive field responses as used in the SIFT and SURF descriptors or their analogues. A notable observation from experimental results is that very good performance can be obtained with coarsely quantized even binary image descriptors (Pietikäinen et al [131], Linde and Lindeberg [88], Calonder et al [26]). Moreover, Zhang et al [158] have demonstrated what can be gained in computer vision by considering biologically inspired image descriptors.…”
Section: Related Workmentioning
confidence: 99%
“…Hall et al [54] computed partial derivatives of colour-opponent channels, leading to an N-jet representation up to order one. Linde and Lindeberg [87,88] extended this idea by showing that highly discriminative image descriptors for object recognition can be obtained from histograms of spatio-chromatic differential invariants up to order two defined from colour-opponent channels. Burghouts and Geusebroek [24] showed that the performance of the SIFT descriptor can be improved by complementing it with a set of colour invariants.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The best results to date come from Linde and Lindeberg, who defined a collection of low-level descriptors, which led to the definition of a multi-dimensional basis for histograms, further reduced by PCA. These histogram descriptions were then optimized via SVM [24].…”
Section: Comparison To Previous Workmentioning
confidence: 99%
“…Operating directly on the original, raw pixel space allows for the extraction of useful low-level patterns and features not captured by traditional vision-based routines. This is now an active area of research, with many strategies being explored, including wavelets, histograms, and others [27,26,8,35,24].…”
Section: Introductionmentioning
confidence: 99%